THE PROBLEM OF CHOICE OF EDUCATION COMMUNICATIVE PARADIGM - Ашиток, Н. І. (Proceedings of the Kyiv Aviation Institute. Series: Philosophy. Cultural, 2015)
In the article the specific character of communication in the system of equipment on the border of millenniums, related to forming of post-nonclassical paradigm is considered.